ESP-Based Needs Analysis for Palu Polytechnic Students - Runggo, Yusniarti; Hendriyani, Hendriyani (research, training and philanthropy institution Natural Aceh, 2025)
English is a compulsory subject that must be taken by every student at Politeknik Palu. The material provided must fit the needs of students and be useful for them. So it is necessary to do a needs analysis so that students get the material they need to support their learning process at this time or in the future. This study was conducted to analyze the need for learning English based on ESP. The research was conducted using descriptive methods and qualitative approaches. The research sample is students who have taken English courses in the Agricultural Products Processing Technology Study Program. Sampling using a purposive random sampling technique. The research instrument used a questionnaire. Data were analyzed using descriptive techniques in the form of numbers and percentages. The results showed that the needs of the Agricultural Products Processing Technology study program students for ESP English courses varied greatly, so it could be concluded that they needed English not only for their current needs but also for future work purposes.